Improvement of Internal Control Through Operational Standards for Procedures for Procurement of The Equipment and Services at 'D' Type Hospital in Sumenep District - Hendy Widiastoeti; Maulidah Narastri (Enrichment : Journal of Management, 2021)
The purpose of this study is to contribute to the Islamic Hospital of Garam Sumenep - Kalianget related to standard operating procedures for procurement of goods and services that are not yet owned or already owned but still need improvements. Standard operational procedures for procurement of goods and services are useful for regulating the implementation of the entry and exit of goods and services and to ensure the smooth and clear mechanism of procurement of goods and services. In addition to standard operational procedures, internal control also functions as a tool to assist management with the aim of achieving a more efficient and effective work mechanism. The research method used by researchers is qualitative with a direct observation approach at the Islamic Hospital of Garam Sumenep - Kalianget. The research team hopes that the standard operational procedures for procurement of goods and services created by the research team can help the Islamic Hospital of Sumenep - Kalianget Garam in managing hospital goods and services both in the short and long term.